Design and fabrication of can crasher - Eddy Ahmadi Azizi, Sukimin (2007)
Creativity of idea is very important in design. It is because, idea is very important to produce a quality, interesting and unique product. As a new product for customer, this can crasher is design followed need characteristic such as easy to handle, multifunction and attractive. In this project, main objective is to create and design a new product based on the existing product in the market. This project are using of various kind of mechanism that have in UMP mechanical laboratory such as mild steel plate, grinding and welding. These can crasher project are used multiple method like measurement, marking, cutting, joining and assembly process. This processes are important because its involve student skill of using a tool and machine. Beside that, it also can make a student learn something new to increase a creativity of thinking and think to produce interesting product for the future market. This product also must have a characteristic like toughness. These projects make the student more discipline, punctuality, create a leadership skills and have a good planning in order that can practice it in real situation at the work place.